Accurate estimation of the photoelectric conversion efficiency of a series of anthracene-based organic dyes for dye-sensitized solar cells. Issue 7 (17th January 2020) - Heng, Panpan; Mao, Lemin; Guo, Xugeng; Wang, Li; Zhang, Jinglai
Abstract : Studies demonstrate that our designed dyes 3 and 4 exhibit broad optical absorption in the 550–650 nm region and high photoelectric conversion efficiencies of over 32%. Abstract : Photoelectric conversion efficiency (PCE) is one of the crucial indicators to determine the overall performance of dye-sensitized solar cells (DSSCs), and accurate estimation of PCE is a feasible strategy for developing high-performance DSSC devices. In this contribution, we strategically designed a series of anthracene-based organic dyes 1–4 by introducing different π-bridge or auxiliary acceptor groups. Their photovoltaic properties were explored by first-principles calculations coupled with the normal model and improved normal model. It is found that the introduction of an electron-rich thieno[3, 2- b ]thiophene-based π-spacer in dye 2 induces a blue-shift of the maximum absorption band with respect to dye 1, while the inclusion of an electron-deficient diketopyrrolopyrrole-based π-bridge in dye 3 and a thieno[3, 4- b ]pyrazine-based auxiliary acceptor in dye 4 can remarkably extend the optical absorption into the 550–650 nm region. In addition, the open-circuit voltage ( V OC ), short-circuit photocurrent density ( J SC ), fill factor (FF) and the corresponding PCE ( η ) were evaluated by the improved normal model. The estimated results of dye 1 ( V OC = 757 mV, J SC = 14.63 mA cm −2, FF = 0.85, and η = 9.41%) reproduce very well the experimentally available data ( V OC = 760 mV, J SC = 14.25 mA cm −2, FF = 0.75, and η = 8.08%), suggesting that the improved normal model is an accurate and general method to predict the photoelectric properties of organic dyes. More importantly, dyes 3 and 4 are predicted to exhibit extremely high PCEs of over 32%, both of which are expected to be potential candidates as metal-free organic dyes applied in DSSCs.